Post-Anesthesia Recovery Experience Following Cesarean Section with ERACS Protocol: A Phenomenological Study in Indonesia - Kurniawan, Arief; Pratiwi, Nur Pudyastuti (Chakra Brahmanda Lentera Institute, 2025)
Background: Enhanced Recovery After Cesarean Section (ERACS) is a perioperative care protocol aimed at improving clinical outcomes and patient experience. Understanding both quantitative outcomes and qualitative experiences is essential to evaluate its comprehensive impact on maternal recovery. Methods: This study was conducted on post-anesthesia cesarean section patients using the ERACS protocol at RS Tk.II 03.05.01 Dustira, Cimahi. In addition to observing clinical parameters such as hemodynamic stability, side effects, and recovery duration, qualitative narratives were collected to explore patient experiences during the recovery process. Results: While the majority of patients were multiparous and of reproductive age with stable intraoperative hemodynamics and low incidence of side effects, the qualitative narratives revealed meaningful insights. Patients described feeling empowered by early mobilization and the ability to initiate immediate breastfeeding (IMD), which enhanced maternal confidence and emotional bonding. Pain reduction and shorter recovery times were viewed not only as clinical improvements but as milestones toward regaining autonomy. The structured ERACS approach and supportive healthcare team fostered a sense of safety and trust. Conclusion: The ERACS protocol contributes to a patient-centered recovery experience that goes beyond clinical outcomes. It enhances emotional well-being, promotes active participation in recovery, and supports the mother’s role from the earliest postpartum moments. These insights suggest that integrating qualitative feedback into clinical protocols can lead to more empathetic, efficient, and personalized perioperative care models.